Effects of Azadirachta excelsa on feeding behaviour, body weight and mortality of Crocidolomia binotalis Zeller (Lepidoptera: Pyralidae) - Ng, Lean Teik; Yuen, Pak Mun; Loke, Wai Hong; Kadir, Azizol Abdul (Wiley, 2003)
We investigated the effects of methanolic extracts of Azadirachta excelsa wood (SWE) at concentrations of 5, 10 and 20 gl-1 against Crocidolomia binotalis. Second instars were fed a diet of cabbage leaves treated with SWE or were contacted topically with SWE. The results indicated that SWE produced significant (p < 0.05) antifeedant and contact toxicity effects. However, among the different treatments, a lesser effect on pupal weight was noted in the contact toxicity test. In most instances, untreated leaves were severely damaged, whereas leaves treated with SWE were not attacked or were only slightly damaged. Although both methods of SWE treatment caused a significantly high mortality rate, there was no difference in dose response in the range studied. Thus SWE at a concentration of 5 gl-1 was shown to be as active as that at 20 gl-1. The results indicate that SWE is a potent antifeedant and also has toxicity against C binotalis.